Unintended consequences of sanitation investment: Negative externalities on water quality and health in India - Kazuki Motohashi (Osaka University, Institute of Social and Economic Research (ISER), 2023)
Developing countries have increased sanitation investment to reduce diarrheal diseases. However, the direct health benefits of latrine construction can be offset by water pollution externalities due to poor treatment of fecal sludge. I estimate these negative externalities of a sanitation policy in India that subsidized the construction of over 100 million latrines. Exploiting geographical variation in soil characteristics and the differential increase in latrine coverage across districts, I find that the policy increases river pollution by 72%. While it reduces diarrheal mortality overall, this positive health effect is two-thirds smaller in areas with lower capacities for treatment of fecal sludge where water pollution externalities are consequently larger.
Keywords: I15; O13; Q53; Q56; 330; Sanitation; Water Quality; Health; Negative Externalities